Sosialisasi Makanan Bergizi Dan Pangan Berimbang Dalam Rangka Pencegahan Stunting Balita Pada Kelompok Wanita Tani (KWT) Bina Karya Di Desa Gunung Sugih Kecamatan Kedondong Kabupaten Pesawaran - Mas Indah, Lidya Sari; Adawiyah, Rabiatul Adawiyah; Seta, Amanda Putra (Agriculture Faculty, Universitas Lampung, 2025)
Abstract: Good food is food that has balanced nutrients. All nutrients have different effects and functions in the human body. Therefore, a deficiency in one nutrient will cause obstacles and health problems, one of which is stunting in toddlers. The objectives of this community service activity were (1) to increase the knowledge of the Bina Karya Women Farmers Group (KWT) on the importance of nutrition and balanced food, and (2) to increase the KWT's knowledge of the dangers and prevention of stunting in toddlers in Gunung Sugih Village, Kedondong District, Pesawaran Regency. The results of this community service activity showed a significant increase in farmers' knowledge regarding the importance of balanced nutrition, as well as the dangers and prevention of stunting. Through this activity, participants gained knowledge about the importance of balanced nutrition from an early age and practical steps in its implementation. This activity had a positive impact in raising public awareness, especially among parents of toddlers, to pay more attention to their children's nutritional intake, optimize the use of local food, and play an active role in stunting prevention efforts. Thus, this activity became an important part of joint efforts to improve the quality of the nation's future generations.